Language Politics and Fiqh’s Authority on Qur'anic Reinterpretation in Indonesian Translation Practices - Musaffa, Muhammad Ulul Albab (Al-Mazaahib: Jurnal Perbandingan Hukum, 2025)
The book Qur'an Translation in Indonesia: Scriptural Politics in a Multilingual State edited by Johanna Pink offers an interdisciplinary analysis of Qur'anic translation practices in Indonesia within the framework of language politics, religious authority, and the articulation of Islamic law (fiqh). Through a variety of historical and contemporary case studies, the book highlights how Qur'ānic translations serve not only as educative tools, but also as instruments of legal orthodoxy through state intervention, school of thought preferences and local dynamics. The review focuses on the aspects of Islamic law that emerge in the choice of diction, the influence of schools of fiqh, and the relationship between tafsir, fatwa, and translation-based legal products. It is concluded that Qur'an translation in Indonesia is a semi-normative practice that is loaded with ideological, legal, and political content, and has a significant impact on the construction of Islamic understanding in contemporary Indonesian Muslim society. Buku Qur’an Translation in Indonesia: Scriptural Politics in a Multilingual State yang disunting oleh Johanna Pink menawarkan analisis interdisipliner mengenai praktik penerjemahan Al-Qur’an di Indonesia dalam bingkai politik bahasa, otoritas keagamaan, dan artikulasi hukum Islam (fikih). Melalui berbagai studi kasus historis dan kontemporer, buku ini menyoroti bagaimana terjemahan Al-Qur’an tidak hanya berfungsi sebagai sarana edukatif, tetapi juga sebagai instrumen pembakuan ortodoksi hukum melalui intervensi negara, preferensi mazhab, dan dinamika lokal. Review ini memfokuskan pada aspek hukum Islam yang muncul dalam pemilihan diksi, pengaruh mazhab fikih, serta relasi antara tafsir, fatwa, dan produk hukum berbasis terjemahan. Disimpulkan bahwa penerjemahan Al-Qur’an di Indonesia merupakan praktik semi-normatif yang sarat dengan muatan ideologis, hukum, dan politik, serta memiliki dampak signifikan dalam konstruksi pemahaman keislaman masyarakat Muslim Indonesia kontemporer.